Pleiotropic Effects of the NSAID Fenamates on Chloride Channels: Opportunity for Ion Channelopathies? - Paola Laghetti; Ilaria Saltarella; Simone Dell'Atti; Jean‐François Desaphy; Concetta Altamura (Pharmacology Research & Perspectives)
ABSTRACT Chloride channels are involved in many cellular processes, including cell volume regulation, modulation of cell excitability, and electrolyte and water secretion. Mutations of these proteins are associated with heterogeneous diseases such as myotonia, cystic fibrosis, epilepsy, deafness, lysosomal storage disease, and various kinds of renal and ophthalmic dysfunctions, also known as channelopathies. Thus, drugs targeting chloride channels may have important therapeutic applications. In this context, fenamates, commonly used for their anti‐inflammatory properties, have been explored for drug repurposing in chloride channelopathies thanks to their ability to modulate multiple chloride channels. This narrative review resumes the effects of niflumic acid (NFA), flufenamic acid (FFA), mefenamic acid (MFA), meclofenamic acid (MCFA), and tolfenamic acid (TFA) on different types of chloride channel. It emerges that fenamates have a wide spectrum of activities on these channels that vary depending on multiple factors like channel isoforms, extracellular and intracellular conditions, and cell and tissue types. They may also exhibit both activating and inhibitory effects depending on their concentration. Therefore, thanks to their variegated modulatory activity on chloride channels, fenamates might be considered promising lead compounds for the development of new drug candidates that can target these altered channels involved in channelopathies. Trial Registration: EudraCT number: 2021‐000708‐39; ClinicalTrials.gov identifier: NCT029930005 and NCT02429570.